ANALYTICAL HIERARCHY PROCESS (AHP) APPROACH ON CONSUMER DECISION MAKING IN SELECTING BANK IN TERMS OF BANK SELECTION CRITERIA - Pangemanan, Berfran Louch (FEB Universitas Sam Ratulangi Manado, 2014)
The Existence of bank is increasing steadily and rapidly since its inception in financial business industry, and has big influence direct to the public. For bank institution, customer is crucial consideration that bank must pay attention carefully. In order to keep existing customers and for attracting new customers, every banks needs to identify the criteria on which customers determine their bank selection decision because in world today especially in Manado customer faces a lots of choice in selecting which bank they want to patronize. Hence, the purpose of this study is to examine the significance of bank selection criteria, and how customers rank the factors based on their importance level to patronize banks and banking services. In this research used Analytical Hierarchy Process (AHP) in processing the data. The population in this research is those who have been customers of the banks PT. Bank Mandiri (Persero) Tbk, PT. BRI (Persero) Tbk, PT. BNI (Persero) Tbk, with purposive sampling to 50 respondents. As the finding, PT. Bank Mandiri becomes the most preferred bank compare to the other two in selecting the best bank. In result of overall criteria, the result shows there are three of seven criteria that have the highest scores, which are bank?s reputation, convenient location by bank, and high interest rate. Moreover, bank?s reputation factor becomes the priority criteria to be considered by customer in process decision- making the best bank. Finally, every company in Manado must give more attention to bank selection especially bank?s reputation, convenient location, and high interest rate as the most influence criteria when people decide to patronize a bank. Keywords: consumer decision making, bank selection.